15 million preterm births annually: what has changed this year? - Kinney Mary V; Lawn Joy E; Howson Christopher P; Belizan José (BMC, 2012)
Abstract Each year, more than 1 in 10 of the world's babies are born preterm, resulting in 15 million babies born too soon. World Prematurity Day, November 17, is a global effort to raise awareness about prematurity. This past year, there has been increased awareness of the problem, through new data and evidence, global partnership and country champions. Actions to improve care would save hundreds of thousands of babies born too soon from death and disability. Accelerated prevention requires urgent research breakthroughs.